POTRET SUBJECTIVE WELL-BEING PADA BHIKKHU DAN ATTHASILANI - Santi Herawati; Arthur Huwae (LPSDI Bina Patria, 2025)
Subjective well-being is an individual's evaluation of their own life, the extent to which their affective judgments and reactions indicate that their life is desirable and going well. It is important to be able to achieve Subjective well-being, especially for Monks and Atthasilani who choose a life of renunciation. This study aims to describe subjective well-being among Bhikkhu and Atthasilani in Indonesia by examining the components and factors that influence it. The research method used is qualitative descriptive phenomenology. Data analysis was carried out iteratively by applying data reduction, data presentation, conclusion drawing, and validation. The results of this study show that both participants have high subjective well-being. Components of subjective well-being, such as life satisfaction, positive affect, and negative affect, are strongly influenced by emotion regulation ability, self-acceptance, and social and spiritual support.